2008
DOI: 10.1007/s00216-008-2437-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical review on recent developments in solventless techniques for extraction of analytes

Abstract: The most recent contributions on solventless extraction techniques have been reviewed. This paper deals with those techniques that use solid phases, such as solid-phase microextraction, liquid phases, such as single-drop microextraction and hollow-fibre liquid-phase microextraction, and subcritical fluids, such as subcritical water extraction. In all cases, the most recent publications have been critically studied. Direct extraction and derivatization processes to facilitate the extraction of analytes in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
137
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(144 citation statements)
references
References 270 publications
0
137
0
3
Order By: Relevance
“…CAR/PDMS extracts with high efficiency ethyl hexanoate (6), p-cymene (9), (Z)-3-hexen-1-ol (13), 2-acetylfuran (24), whereas PDMS is more indicated to extract 1-dodecene (19), decanal (22), ␣-ionol (43), diethyl malate (46), and octanoic (47), tetradecanoic (55), and hexadecanoic acids (56). PA …”
Section: Hs-spme Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CAR/PDMS extracts with high efficiency ethyl hexanoate (6), p-cymene (9), (Z)-3-hexen-1-ol (13), 2-acetylfuran (24), whereas PDMS is more indicated to extract 1-dodecene (19), decanal (22), ␣-ionol (43), diethyl malate (46), and octanoic (47), tetradecanoic (55), and hexadecanoic acids (56). PA …”
Section: Hs-spme Analysismentioning
confidence: 99%
“…Is a miniaturization of the conventional SPE in which the sample volume and volumes for extraction and washing solvents are reduced compared to SPE technique [19] (Table 2). A wide range of sorbents are available including C 2 , C 8 and C 18 bonded phases on silica, polymeric resins (polystyrene/divinylbenzene copolymer), molecular imprinted polymers (MIPs), polar sorbents such as silica and ion-exchange sorbents, and mixed-mode sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Researching the drug transfer process in this novel device is necessary for supporting the control method for cell pulse dosing. It is known that the mass transfer between deionized water droplets and continuous phases octanol can be observed that there is a vortex on the surface of the microdroplets [24] and the solute transfer at the instantaneous two-phase interface is proportional to the square of the time [25]. The drug diffusion to cells through microporous membrane from microdroplet surround by oil is influenced by these factors, especially the mechanism of mass transfer through membrane in fluid.…”
Section: Introductionmentioning
confidence: 99%
“…There are as many as 1018 kinds of ionic liquids available in literature [16]. Recently, room temperature ionic liquids with unique properties such as negligible vapour pressure, water stability, favourable viscosity and density characteristics, good thermal stability, non-volatility and good selective solubility have been used as alternative solvents separation purposes [17,18].…”
Section: Introductionmentioning
confidence: 99%